Italy : Technical Assistance Report--The Delega Fiscale and the Strategic Orientation of Tax Reform. (IMF Staff Country Reports; Country Report, 2012)
The contents of this report constitute technical advice provided by the staff of the International Monetary Fund (IMF) to the authorities of Italy (the 'TA recipient') in response to their request for technical assistance. This report (in whole or in part) or summaries thereof may be disclosed by the IMF to IMF Executive Directors and members of their staff, as well as to other agencies or instrumentalities of the TA recipient, and upon their request, to World Bank staff and other technical assistance providers and donors with legitimate interest, unless the TA recipient specifically objects to such disclosure (see Operational Guidelines for the Dissemination of Technical Assistance Information: http://www.imf.org/external/np/pp/eng/2009/040609.pdf">http://www.imf.org/external/np/pp/eng/2009/040609.pdf). Disclosure of this report (in whole or in part) or summaries thereof to parties outside the IMF other than agencies or instrumentalities of the TA recipient, World Bank staff, other technical assistance providers and donors with legitimate interest shall require the explicit consent of the TA recipient and the IMF's Fiscal Affairs Department.